Charming Ice Sdn.Bhd / Hafizuddin Zainal Arifin... [et.al] - Zainal Arifin, Hafizuddin; Sekudan, Jacquellyn Albert; John, Sainti; Inang, Olivia (2011)
Once a maxim have said 9/10 of the sources of wealth in this world are by doing business. Thus, we decided to open our own business. Our company, Charming Ice is based on the partnership business venture in the food and beverages industry. We open our own cafe and serve our customers with our ice cream. We producing high quality of ice cream which using only high quality of raw materials and we using our own recipes in making ice cream. Besides, we try to serve our customers with friendly service and ensure that our service and product will meet and exceed their satisfaction. The comfort of our customer is our main objectives. Our business is in form of partnership which consists of four shareholders. All shareholders had agreed as stated in agreement letter which the amount of capital, profit and loss will be divided equally as stated ratio. We chose this kind of business because it shows the equality and no one will be discriminated as the profits and losses are equally divided in the end of the accounting period. In other way, the partnership is a perfect option to be taken because the shareholders will always sharing ideas and knowledge in order to gain profit and achieve high productivity from time to time.